2004
DOI: 10.1016/j.febslet.2004.06.009
|View full text |Cite
|
Sign up to set email alerts
|

The influence of dipeptide composition on protein thermostability

Abstract: In this work, the influence of dipeptide composition on protein thermostability was studied. After comparing the normalized dipeptide composition between mesophilic proteins and (hyper)thermophilic proteins, we concluded that when organism optimal growth temperature increased, for archaeal proteins, the compositions of VK, KI, YK, IK, KV, KY, and EV increased significantly and the compositions of DA, AD, TD, DD, DT, HD, DH, DR, and DG decreased significantly; and for bacterial proteins, the compositions of KE,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(28 citation statements)
references
References 14 publications
2
26
0
Order By: Relevance
“…Among the 400 dipeptides, thermophilic proteins contained more EE, KK, RR, PP, KI, VV, VE, KE and VK, while mesophilic proteins contained more QQ, AA, EQ, LL, QA, QL, NN, KQ, QG, RQ, QTand AQ. Our results were consistent with a previous report [9] that thermophilic proteins had significantly higher dipeptide composition of EE, KK, KI, VE, KE and VK, lower dipeptides compositions of QQ, AA, QA, QL, RQ and AQ. But other dipeptides were not in the list of their characteristic dipeptides correlative to protein thermostability.…”
Section: Dipeptide Composition In Thermophilic and Mesophilic Proteinsupporting
confidence: 95%
See 1 more Smart Citation
“…Among the 400 dipeptides, thermophilic proteins contained more EE, KK, RR, PP, KI, VV, VE, KE and VK, while mesophilic proteins contained more QQ, AA, EQ, LL, QA, QL, NN, KQ, QG, RQ, QTand AQ. Our results were consistent with a previous report [9] that thermophilic proteins had significantly higher dipeptide composition of EE, KK, KI, VE, KE and VK, lower dipeptides compositions of QQ, AA, QA, QL, RQ and AQ. But other dipeptides were not in the list of their characteristic dipeptides correlative to protein thermostability.…”
Section: Dipeptide Composition In Thermophilic and Mesophilic Proteinsupporting
confidence: 95%
“…Gromiha et al [8] made a comparative analysis on the relation between thermostability and amino acid properties for a family of meso-and thermophilic proteins wherein the Gibbs free energy change of hydration and shape play a dominant role in thermostability of proteins. But from the diverse collection of studies, it is difficult to find out the influence of dipeptide composition on protein thermostability [9]. In fact, the proteins which have similar amino acid composition may vary in dipeptide composition, meanwhile, amino acids may function with the cooperation of other residues nearby in sequence or space, so the function of a specific amino acid was influenced by its neighboring amino acid in sequence or in space, while dipeptide can reflect the influence in sequence.…”
Section: Introductionmentioning
confidence: 98%
“…Ding et al (2004) have analyzed the single amino acid composition of 20653 archaeal protein sequences including the sequences from mesophilic (optimal temperature between 20 and 50°C), thermophilic and (optimal temperature between 50 and 80°C) hyperthermophilic proteins (optimal temperature between 80 and 120°C). They concluded that for archaeal proteins, the compositions of Lys and Arg increased when the optimal growth temperature increased, while the compositions of Asp, Thr, Gln, and His decreased when the optimal growth temperature increased.…”
Section: P-np P-nitrophenylmentioning
confidence: 99%
“…However, it was difficult to find the influence of dipeptide composition on protein thermostability [10] from the diverse collection of studies. Proteins that have similar amino acid composition vary in dipeptide composition; while, amino acids function with the help of other residues nearby in sequence or space.…”
Section: Introductionmentioning
confidence: 99%